Формирование шероховатости поверхности деталей машин в процессе шлифования - Кленов, Олег Станиславович; Дитиненко, Станислав Александрович; Крюк, Анатолий Григорьевич; Новиков, Федор Васильевич (НТУ "ХПИ", 2017)
Приведены аналитические зависимости для определения шероховатости поверхности при шлифовании, полученные на основе теоретико-вероятностного подхода при моделировании режущих зерен круга в форме конуса и сферы. Показано, что моделирование режущих зерен круга в форме сферы приводит к заниженным значениям, а в форме конуса – к завышенным значениям шероховатости поверхности по сравнению с экспериментальными данными. Поэтому при расчете шероховатости поверхности режущие зерна круга следует рассматривать в форме усеченного конуса, учитывая размеры образующейся площадки износа на зерне.

Analytical dependences are given for determining the surface roughness during grinding, obtained on the basis of the theoretical-probabilistic approach in the modeling of the cutting grains of a circle in the form of a cone and a sphere. It is shown that the modeling of the cutting grains of a circle in the form of a sphere leads to underestimated values, and in the form of a cone – to overestimated values of the surface roughness in comparison with the experimental data. Therefore, to determine the roughness parameters of the surface when grinding with a diamond circle after dressing, it is suggested that the grains be considered in the form of a cone, and after the running-in of a circle, in the form of a sphere. When the roughness of the surface is refined, the cutting grain of the circle should be considered in the form of a truncated cone, taking into account the dimens ions of the wear area on the grain, using a dimensionless coefficient equal to zero for the sharpened grain and varying within 0 ... 1 for worn-out grain. Based on the results of the research, practical recommendations are given to reduce the surface roughness during grinding.
Forming of a roughness of a surface of details of machines in the course of grinding
Keywords: режущие зерна круга; конус; сфера; площадка износа; теоретико-вероятностный подход; cutting circle grains; cone; sphere; wear surface; probability-theoretic approach